Challenges facing teachers in developing financial awareness among kindergarten children - Aldossary, Norah Saleh Abdullah; Etman, Ali Abd Eltawab Mohamed; Omar, Sahar Mansour Sayed (Journal of Posthumanism, 2025)
The study aimed to identify the challenges facing female teachers in developing financial awareness among kindergarten children in Najran city, Kingdom of Saudi Arabia. The study sample included (109) kindergarten teachers from kindergarten institutions in Najran city, Kingdom of Saudi Arabia. They were randomly selected from government kindergarten institutions. The study was conducted during the second semester of the academic year (2024/2025). The objectives were set to identify the challenges facing kindergarten teachers in developing financial awareness among children. The descriptive analytical approach was used, as the study included a questionnaire directed at kindergarten teachers to identify the challenges facing teachers in developing financial awareness among kindergarten children in Najran city. The questionnaire contained (6) paragraphs related to the challenges facing teachers in developing financial awareness among kindergarten children in Najran city. The researchers used the theoretical framework, previous studies, and specialized experience in raising children in the early childhood stage to develop the questionnaire. The results were processed using the SPSS statistical program, and the study reached the following conclusions: Availability of educational materials and tools that support the development of financial awareness in children.